2022
DOI: 10.1155/2022/4962753
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] A Study on the Application Model of Blended Teaching in English Language Teaching in Colleges and Universities under the Ecological and Internet Perspectives

Abstract: In order to better adapt to the relevant requirements of blended teaching in colleges and universities under the ecological environment and in the “Internet +” era, the “online + offline” blended teaching mode of college English in the Internet era is innovated to further highlight the subjectivity of students in the process of English learning status. First, this study deeply understands the current situation and problems of College English teaching from the perspective of the Internet by means of a questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Research findings indicate that audio-video materials can effectively address students' English speaking issues Li (2022), while online authentic materials have proven highly advantageous in improving students' English proficiency (Qiu, 2022). Other technology-supported instructional methods, such as mobile applications and augmented listening and speaking activities, contribute significantly to enhancing students' engagement, motivation, and selfregulation (Tao, 2020;Sun, 2018;Ma, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Research findings indicate that audio-video materials can effectively address students' English speaking issues Li (2022), while online authentic materials have proven highly advantageous in improving students' English proficiency (Qiu, 2022). Other technology-supported instructional methods, such as mobile applications and augmented listening and speaking activities, contribute significantly to enhancing students' engagement, motivation, and selfregulation (Tao, 2020;Sun, 2018;Ma, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%